Ethnographic Perspectives on Gender-Based Violence in Colombia: Voices and Testimonies from Everyday Life - Ortega, José Marcelo Torres; Murillo , Hernán Javier Guzmán; Barros, María Claudia Pacheco; Meza, Yuraima Yuliza Hernández; Padrón, Julio Cesar Cantillo (Journal of Ecohumanism, 2024)
This study explores gender-based violence in Colombia from a qualitative ethnographic research approach, focused on the reports and experiences of women who have experienced situations of violence in different social and community contexts. Through the application of in-depth interviews, focus groups, and participant observation, qualitative data were collected that allow us to understand the sociocultural dynamics that perpetuate this problem. The results reveal that patriarchal structures and cultural norms influence the normalization of violence, and that women face symbolic and material barriers to accessing justice and obtaining institutional support. In addition, patterns of justification of violence based on emotional dependence and psychological manipulation were identified, which reinforces the need to implement educational and early awareness programs. This study highlights the importance of listening to women’s voices and building a comprehensive approach that addresses gender-based violence from an intersectional perspective, recognizing the different ways in which it manifests itself in family, work, and community spaces.